Effectiveness of cognitive behavioral therapy for major depression in stage II pancreatic cancer patients from the Clínica General del Norte in Barranquilla, Colombia - Cure, H. (The Young Researcher)
Depression is a disorder with specific symptoms that include prolonged periods of sadness. Oncologic (cancer) patients usually present depressive symptoms due to the effects of cancer and the aggressive treatments that can take a toll on their health. Additionally, pancreatic cancer can induce a significant amount of psychological distress in its patients. For this reason, this qualitative content analysis study aims to determine if cognitive behavioural therapy is the most effective treatment for major depression, characterized by at least two weeks of low-mood, in stage II pancreatic cancer patients. Cognitive behavioural therapy focuses on making patients understand that their thoughts can influence their emotions, which then ends up influencing behaviour and affecting relations. The responses to 16 semi-structured post-treatment interviews are assessed in order to determine the effectiveness of the therapy. Cognitive behavioural therapy was able to address main issues in oncologic patients, such as fostering new optimistic perspectives (81.25%), providing empathetic listening (75.00%), and helping patients feel calmed (68.75%). These results suggest that cognitive behavioural therapy is effective for treating major depression in stage II pancreatic cancer patients.